Characterization of Biodiesel Quality from Transesterification of Palm Oil Using Homogeneous Catalysts KOH and NaOH - Endah Kusuma Rastini; Jimmy Jimmy (Universitas Tribhuwana Tunggadewi Malang, 2022)
Biodiesel is a renewable fuel as an alternative fuel in diesel engines. Its use can be combined with petrodiesel. Making biodiesel with a homogeneous catalyst (KOH/NaOH) requires low production costs. This research was conducted to determine the physical and chemical characteristics of biodiesel products using a homogeneous catalyst from food-grade palm oil, which was worked at room temperature, with a stirring time of 8 minutes (200 rpm), the reaction time of 4 hours with a mole ratio of methanol: oil 6:1. The results of the feasibility test for density (KOH 859 kg/m3, NaOH 868 kg/m3) and viscosity (KOH 2.70 cSt, NaOH 3.08 cSt) show that biodiesel meets the quality requirements of biofuels. FFA feasibility test results, acid number, total glycerol, saponification number, and alkyl ester content for biodiesel with KOH catalyst (0.205%, 0.3716 mg ̶ KOH/g, 0.012% ̶ mass, 58.99 mg ̶KOH/g, 99.074% ̶mass, respectively) has met the quality requirements. However, the glycerol content for NaOH has not met the quality requirements for biofuels, so it is necessary to review the optimum conditions. Further testing of biodiesel quality by applying it to diesel engines is required for production feasibility. ABSTRAKBiodiesel merupakan bahan bakar terbarukan sebagai alternatif bahan bakar pada mesin diesel. Penggunaannya dapat dikombinasi dengan petrodiesel. Pembuatan biodiesel dengan katalis homogen (KOH/NaOH) memerlukan biaya produksi yang murah. Penelitian ini dilakukan untuk menentukan karakteristik fisika dan kimia produk biodiesel dengan katalis homogen dari minyak kelapa sawit food grade yang dikerjakan pada temperatur kamar, waktu pengadukan 8 menit (200 rpm), waktu reaksi 4 jam dengan rasio mol methanol:minyak 6:1. Hasil pengujian kelayakan terhadap massa jenis (KOH 859 kg/m3, NaOH 868 kg/m3) dan viskositas (KOH 2,70 cSt, NaOH 3,08 cSt) menunjukkan bahwa biodiesel telah memenuhi syarat mutu bahan bakar nabati. Hasil pengujian kelayakan FFA, bilangan asam, gliserol total, bilangan penyabunan dan kadar ester alkil untuk biodiesel dengan katalis KOH (berturut-turut 0,205%, 0,3716 mg ̶ KOH/g, 0,012% ̶ massa, 58,99 mg ̶ KOH/g, 99,074% ̶ massa) telah memenuhi syarat mutu, namun untuk NaOH kadar gliserol belum memenuhi syarat mutu bahan bakar nabati sehingga perlu dikaji ulang kondisi optimumnya. Pengujian lanjutan kualitas biodiesel dengan mengaplikasikan pada mesin diesel diperlukan untuk kelayakan produksi.